(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we are discussing porting methods of Linux console based applications to android platform and primarily concentrating on migration of Hadoop from personal computer to android device. There are four different approaches towards porting methodology [1] viz. recompilation of Linux binaries using bionic c library, running android under Linux, running Linux in android environment, and Virtualization method of multiple virtualized Linux running parallel. We are focusing on implementation of Linux with help of ‘chroot’ method. This paper specifically discuss the ‘Hadoop’ migration to an Android device. Hadoop being important factor of big data processing, provides a flexible MapReduce Implementation. With this port, it would be easier to minimize cost of cluster formation. We are also discussing pseudo-distributed node formation on this ported Hadoop.